The archaeologist's fieldwork guide - Kipfer, Barbara Ann (Wiley-Blackwell, 2023)
Firstly published in 2006 in hardcover and paperback spiral, The Archaeologist's Fieldwork Companion is the only current one-volume collection of the practical information and material needed by archaeologists doing fieldwork. Designed as concise informational toolkit to be carried into the field, the book is geared to quick reference thanks to its encyclopedia-like format, offering invaluable aid not only to students undertaking fieldwork for the first time, but also to seasoned archaeologists. Fieldwork is still one of the biggest challenge and learning curve for archaeology and anthropology students. Building on the success of the first edition, the new textbook aims to keep guiding early undergraduates and researchers at any level to design and perform fieldwork projects, providing lists and checklists, recording and measurement charts and tables, analysis and classification guides, information on drafting and artifact drawing, and much more. The already exhaustive content will be fully revised and updated to include new materials on technology and most recent systems and tools (like GIS, 3D data capture and modelling, DNA extraction, LiDAR scanning, drone use, underground mapping). New topics of emerging interest like community engagement and public archaeology will also be covered to reach a diverse range of readers and capitalize on the appeal of the book in international markets. Designed to provide students and researchers at any level with a welcoming and accessible guide to the practice of fieldwork, this textbook is the perfect primary or supplementary manual for archaeology, anthropology and cultural resource management (CRM) courses"--